Insulin clearance and incretin hormones following oral and “isoglycemic” intravenous glucose in type 2 diabetes patients under different antidiabetic treatments - Andrea Tura; Christian Göbl; Irfan Vardarli; Giovanni Pacini; Michael Nauck (Scientific Reports, 2022)
Abstract It has not been elucidated whether incretins affect insulin clearance in type 2 diabetes (T2D). We aimed exploring possible associations between insulin clearance and endogenously secreted or exogenously administered incretins in T2D patients. Twenty T2D patients were studied (16 males/4 females, 59 ± 2 years (mean ± standard error), BMI = 31 ± 1 kg/m2, HbA1c = 7.0 ± 0.1%). Patients were treated with metformin, sitagliptin, metformin/sitagliptin combination, and placebo (randomized order). On each treatment period, oral and isoglycemic intravenous glucose infusion tests were performed (OGTT, IIGI, respectively). We also studied twelve T2D patients (9 males/3 females, 61 ± 3 years, BMI = 30 ± 1 kg/m2, HbA1c = 7.3 ± 0.4%) that underwent infusion of GLP-1(7–36)-amide, GIP, GLP-1/GIP combination, and placebo. Plasma glucose, insulin, C-peptide, and incretins were measured. Insulin clearance was assessed as insulin secretion to insulin concentration ratio. In the first study, we found OGTT/IIGI insulin clearance ratio weakly inversely related to OGTT/IIGI total GIP and intact GLP-1 (R2 = 0.13, p < 0.02). However, insulin clearance showed some differences between sitagliptin and metformin treatment (p < 0.02). In the second study we found no difference in insulin clearance following GLP-1 and/or GIP infusion (p > 0.5). Thus, our data suggest that in T2D there are no relevant incretin effects on insulin clearance. Conversely, different antidiabetic treatments may determine insulin clearance variations.